49x² - .......... = (....... + 3)(....... - 3)
a² - b² = (a + b) (a - b)
donc :
49x² - 9 = (7x + 3) (7x - 3)
tu essayes de continuer ?
........... + 10x + .......... = (x + ........)²
a² + 2ab+ b² = (a + b)²
donc : .........si 2ab = 10x, alors a=x et b =5
donc : x² + 10x + 25 = (x+5)²
........ - 42x + 49 = (....... - .......) ²
a² - 2ab + b² = (a - b)²
donc : ..............si b² = 49, alors b=...... et, si 2ab = 42x, alors b=7 et a=3
x² - ............ + 64 = (....... - ........)²
a² - 2ab + b² = (a + b)²
donc: .............